Cuz I love you [compact disc] - Lizzo, 1988- (Atlantic, 2019)
Channeling boundless self-confidence through a downright earth-quaking voice, colorful persona, and undeniable star power, Lizzo struts into the spotlight and steps up with a whole lot of sass, spirit, and soul. Embracing her vocal range like never before and celebrating herself to the fullest, she speaks her mind, censors nothing, and delivers an enviable level of honesty, pure passion, and fresh fire.